1977
DOI: 10.1111/j.1432-1033.1977.tb11550.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Long-Chain Fatty Acids. Incorporation of Radioactivity from Stereospecifically Tritiated Malonyl Thiol Esters, and the Stereochemistry of the Acetyl-CoA Carboxylase Reaction

Abstract: 1. Fatty acid synthetase was purified to homogeneity from bakers' yeast. (2S,3R)-[3-3H~]Malic acid was prepared by incubation of fumarate with fumarase in tritiated water.3. [2-3H1 ,3-3H~]Fumarate was synthesised via a published procedure and used for the preparation of (2S,3S)-[2-3H~,3-3Hl]malate by incubation with fumarase in water.4. The above malates after being mixed with [U-14C]malate were converted into the 4-nitrophenyl hydrogen malates esterified at the C-4 carboxyl, the C-1 carboxyl and the 2-hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…Because it is observed for the pro-R position of the even CH 2 groups that the participation of water clearly increases (a ij Ï­ 0.72; see Equation 16), whereas those of the H-6,6 and H-1 of glucose strongly decrease (0.08; see Equation 17, and 0.01; see Equation 18, respectively), it can be concluded that a major exchange of hydrogen atoms from the CH 3 of acetate with the medium water during chain elaboration has occurred. Thus, post-malonate exchange (10,11), taking place after the formation of malonyl-CoA, is found to strongly influence the hydrogen linkage in the pro-R position of even sites. This process has been described as very variable (11,12,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is observed for the pro-R position of the even CH 2 groups that the participation of water clearly increases (a ij Ï­ 0.72; see Equation 16), whereas those of the H-6,6 and H-1 of glucose strongly decrease (0.08; see Equation 17, and 0.01; see Equation 18, respectively), it can be concluded that a major exchange of hydrogen atoms from the CH 3 of acetate with the medium water during chain elaboration has occurred. Thus, post-malonate exchange (10,11), taking place after the formation of malonyl-CoA, is found to strongly influence the hydrogen linkage in the pro-R position of even sites. This process has been described as very variable (11,12,39,40).…”
Section: Discussionmentioning
confidence: 99%
“…1). However, the isotope redistribution coefficients from acetate will be diminished if post-malonate exchange with medium occurs (10,11). At odd sites (derived from the CÏ­O of acetate), the hydrogen atoms are introduced by the 3-oxoacyl-CoA reductase and the enoyl reductase, both linked to glucose via the NAD(P)H pool (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the C-1, C-2, C-6, and C-9 methine groups contained no deuterium although also derived from the methyl group of acetate. Acetyl coenzyme A -malonyl coenzyme A interconversion (23) can account for loss of deuterium at the acetyl groups but the complete removal of deuterium at other sites suggests facile exchange between the protons of water and the deuterium at activated methylene groups in malonyl coenzyme A (24,25) or in the polyketide chain bound to the enzyme surface. The presence of deuterium at the methyl groups of 6 but not elsewhere was also confirmed by the 'H spectrum, in which signals (intensity I,,) arising from deuteriums bonded to 13C of the methyl groups were well separated by 13C-'H coupling from the corresponding signal (intensity I,,) of 'H bonded to 12C.…”
Section: Assembly Pattern Of Acetate In 3 Andmentioning
confidence: 99%
“…Cornforth then turned 43 his attention to the formation of the mevalonic acid precursor, 3-hydroxy-3-methylglutaryl co-enzyme A and to the chain elongation steps (49 → 52) of fatty acid biosynthesis 44,45 . For this he used the enantiomers of malonyl co-enzyme A 50 which, in fatty acid biosynthesis, is formed by the carboxylation of acetyl co-enzyme A.…”
Section: Some Applications Of the Chiral Methyl Group In Biosyntheticmentioning
confidence: 99%